1. The problem statement, all variables and given/known data Let T:R->R^2 be the linear transformation that maps the point (1,2) to (2,3) and the point (-1,2) to (2,-3). Then T maps the point (2,1) to ... 2. Relevant equations T(xa+yb) = xT(a)+yT(b) 3. The attempt at a solution Okay so I have the solution to this problem, but its understanding some multiplication that's getting me. They get x=5/4 and y = -3/4 and they do the following T(c) = xT(a) +yT(b) T(21)=(5/4)T(12)-(3/4)T(-12) (5/4)(23)-(3/4)(2-3) (16) I just need someone to explain to me how they got the 1 and 6 at the end.